High-conductivity anti-freezing organic hydrogel, preparation method and device

By using a combination of PEDOT:PSS self-supporting film and antifreeze agent in antifreeze hydrogels, the problem of low conductivity of existing antifreeze hydrogels is solved, and a combination of high conductivity and freeze resistance is achieved, which is suitable for applications in extreme environments.

CN119857439APending Publication Date: 2025-04-22XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510014115.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing anti-freeze hydrogels have low conductivity, limiting their application in extreme environments.

Method used

A high conductivity anti-freeze organic hydrogel was prepared by mixing the PEDOT:PSS aqueous solution with the dopant, and immersing it in the aqueous solution of the antifreeze after annealing.

Benefits of technology

It achieves high conductivity (up to 728.51S/cm) and good frozen resistance, so that the conductivity of hydrogels does not change much under low temperature conditions, and is suitable for applications in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857439A_ABST
    Figure CN119857439A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductor thermoelectric materials, and discloses a high-conductivity anti-freezing organic hydrogel, a preparation method and a device, and the preparation method comprises the steps: mixing PEDOT: PSS with a dopant, then dispensing the mixture on a substrate, and drying to obtain a PEDOT: PSS self-supporting film; and annealing the PEDOT: PSS self-supporting film, and immersing the PEDOT: PSS self-supporting film into an organic anti-freezing agent solution to obtain the high-conductivity anti-freezing organic hydrogel. The hydrogel is cut into long strips, and the long strips are connected through conductive silver paste or copper foil to obtain the device. The hydrogel material with the conductivity of 698.26 + / -37.27 S / cm is successfully prepared and is applied to preparation of thermoelectric devices, and the devices have excellent output power at the temperature of about-70 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor thermoelectric materials, and in particular relates to a high-conductivity antifreeze organic hydrogel and a preparation method and a device. Background Art

[0002] Hydrogels are expected to be used in fields such as smart driving, wearable electronics, and tissue engineering because they have a Young's modulus similar to that of biological tissues. However, due to their high water content, hydrogels inevitably face the disadvantage of poor low-temperature resistance. Most hydrogels are frozen under low-temperature conditions (for example, temperatures below zero degrees Celsius), resulting in the reduction of hydrogels' elasticity [Adv. Sci., 2022, 9(29), e2202644, Nano Converg, 2022, 9(1), 18, Sustain. Mater. Technol., 2022, 32, 32e00437] and electrical conductivity [J. Mater. Chem. A, 2022, 10(48), 25527–25538, J. Mater. Chem. A, 2022, 10(41), 21874–21883] and other properties, limiting the application of hydrogels in extreme environments. At the same time, most hydrogels have ions as charge carriers and low electrical conductivity, which will also limit the application of hydrogels. Therefore, it is necessary to develop antifreeze hydrogels with high electrical conductivity.

[0003] At present, the methods for preparing antifreeze hydrogels usually include: introducing inorganic salts, ionic liquids, zwitterions or organic solutions into the hydrogel to lower the freezing point of the hydrogel. For example, by introducing the inorganic salt sodium citrate into the hydrogel, the citrate ions and sodium ions will hinder the aggregation of water molecules and hinder the formation of ice lattices, thereby lowering the freezing point of the hydrogel, so that the hydrogel still has a tensile strain of 139% at -50°C [Chemical Engineering Journal 403(2021)126431]. By introducing the inorganic salt lithium chloride into the hydrogel, lithium ions and water molecules form Li + (H2O)n hydrated structure makes the hydrogel show excellent antifreeze and anti-drying properties. The hydrogel remains flexible and conductive at -20°C [Adv.Funct.Mater.2024,2314419]. When zinc perchlorate solution is introduced into the hydrogel, perchlorate anions, water and polymer chains form ternary and weak hydrogen bonds, destroying the hydrogen bonds of water, thereby significantly reducing the freezing point of the hydrogel. The hydrogel still has 7.8mS cm even at -30°C. -1High ionic conductivity [Adv.Mater.2022,34,2110140]. Zwitterionic betaine and inorganic salt ammonium sulfate enable the hydrogel to withstand low temperatures of -40°C [Chemical Engineering Journal 452(2023)139314]. The organic solvent propylene glycol is introduced into the hydrogel to form a large number of hydrogen bonds between propylene glycol and water, which limits the crystallization of water, lowers the freezing point of the hydrogel, and the hydrogel remains flexible at -50°C [ACS Appl. Mater. Interfaces 2023,15,24175-24185]. Although the above methods improve the antifreeze properties of the hydrogel, since most of the research is based on ionic gels such as polyacrylamide, polyacrylic acid or polyvinyl alcohol, the conductivity of this antifreeze hydrogel is very low, mostly <10S / cm. Summary of the invention

[0004] In order to overcome the problem of low conductivity of antifreeze hydrogels in the prior art, the purpose of the present invention is to provide a high-conductivity antifreeze organic hydrogel and a preparation method and a device. The organic hydrogel prepared by the method has high conductivity and antifreeze performance.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing a high-conductivity antifreeze organic hydrogel comprises the following steps:

[0007] The PEDOT:PSS aqueous solution is mixed with the dopant, then drop-coated on a substrate and dried to obtain a PEDOT:PSS free-standing film;

[0008] After annealing, the PEDOT:PSS self-supporting film was immersed in an aqueous solution of an antifreeze agent to obtain a high conductivity antifreeze organic hydrogel.

[0009] Furthermore, the amount of the dopant is 10-50% of the mass of PEDOT:PSS.

[0010] Furthermore, the dopant is lithium bis(trifluoromethylsulfonyl)imide.

[0011] Furthermore, the antifreeze agent is glycerol, ethylene glycol or polyethylene glycol.

[0012] Furthermore, the concentration of the aqueous solution of the antifreeze agent is 0wt.%-100wt.%.

[0013] Furthermore, before annealing the PEDOT:PSS self-supporting film, the PEDOT:PSS self-supporting film was immersed in ethanol.

[0014] Furthermore, the annealing conditions are: annealing is performed 3 times at 130-140° C. with a cycle of 15 minutes.

[0015] Furthermore, after the PEDOT:PSS self-supporting film is annealed, it is immersed in an aqueous solution of an antifreeze agent for 30-60 seconds.

[0016] A high-conductivity antifreeze organic hydrogel, wherein the maximum conductivity of the organic hydrogel is 728.51 S / cm.

[0017] A thermoelectric device, comprising a high-conductivity antifreeze organic hydrogel prepared according to the method according to any one of claims 1 to 8.

[0018] Compared with the prior art, the present invention has significant beneficial effects:

[0019] The present invention prepares a PEDOT:PSS hydrogel without adding an inorganic conductive filler. First, PEDOT:PSS is treated with a dopant so that PEDOT and PSS are phase separated, and the conductive PEDOT part is aggregated to improve the conductivity of the self-supporting film. The self-supporting film is then further annealed to improve the crystallinity of the self-supporting film, thereby improving the conductivity. The self-supporting film is then immersed in an antifreeze aqueous solution of a certain concentration to prepare the self-supporting film into a hydrogel, and the hydrogel has antifreeze properties. The organic hydrogel prepared by this method not only has high conductivity (conductivity as high as 698.26±37.27S / cm) but also has good antifreeze properties, and the conductivity is higher than that of pure PEDOT:PSS hydrogel reported previously.

[0020] Furthermore, the dopant is lithium bis(trifluoromethylsulfonyl)imide having negative ion exchange free energy with PEDOT:PSS, and the dopant is used to phase separate PEDOT and PSS.

[0021] Furthermore, the self-supporting film was immersed in ethanol to remove the non-conductive PSS part in the film and further improve the conductivity of the film.

[0022] The thermoelectric device prepared by using the high-conductivity antifreeze organic hydrogel in the present invention has excellent output power at about minus 70°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Flow chart for the preparation of antifreeze and high-conductivity PEDOT:PSS organic hydrogel.

[0024] Figure 2The conductivity and Seebeck coefficient of the prepared antifreeze high conductivity PEDOT:PSS organic hydrogel, wherein (a) is the conductivity and Seebeck coefficient of the prepared organic hydrogel with different propylene glycol contents, (b) is the conductivity and Seebeck coefficient of the prepared organic hydrogel with different polyethylene glycol contents, and (c) is the conductivity and Seebeck coefficient of the prepared organic hydrogel with different ethylene glycol contents.

[0025] Figure 3 A comparison chart of the conductivity of the prepared antifreeze and high-conductivity PEDOT:PSS organic hydrogel and the literature.

[0026] Figure 4 The figures are cross-sectional scanning electron micrographs of the prepared antifreeze high-conductivity PEDOT:PSS organic hydrogels, wherein (a) is a cross-sectional scanning electron micrograph of a hydrogel containing 0 wt.% of antifreeze glycerol, (b) is a cross-sectional scanning electron micrograph of an organic hydrogel containing 10 wt.% of antifreeze glycerol, and (c) is a cross-sectional scanning electron micrograph of an organic hydrogel containing 100 wt.% of antifreeze glycerol.

[0027] Figure 5 Differential scanning calorimetry spectrum of the prepared antifreeze and high conductivity PEDOT:PSS organogel.

[0028] Figure 6 This is a graph showing the change in conductivity of the antifreeze high-conductivity PEDOT:PSS organogel prepared in Example 1 at conditions below room temperature.

[0029] Figure 7 The thermoelectric device is prepared by using the antifreeze high conductivity PEDOT:PSS organogel of Example 1.

[0030] Figure 8 The performance diagram of the prepared thermoelectric device under certain temperature difference conditions is shown in the figure, with the room temperature fixed as the hot end and the temperature of the cold end adjusted. Among them, (a) is the current-voltage diagram of the prepared thermoelectric device by immersing the self-supporting film prepared by the dopant Li-TFSI in a 100wt.% glycerol solution in the organic gel, (b) is the load resistance-output power diagram of the prepared thermoelectric device by immersing the self-supporting film prepared by the dopant Li-TFSI in a 100wt.% glycerol solution in the organic gel, (c) is the voltage-output power diagram of the prepared thermoelectric device by immersing the self-supporting film prepared by the dopant Li-TFSI in a 100wt.% glycerol solution in the organic gel; DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0032] The method for preparing the high-conductivity antifreeze organic hydrogel of the present invention comprises taking PEDOT:PSS as the main body, adopting ionic liquid as a dopant to dope the PEDOT:PSS solution, and then preparing a PEDOT:PSS self-supporting film, and immersing the PEDOT:PSS self-supporting film in an aqueous solution of an antifreeze agent to prepare a PEDOT:PSS antifreeze organic hydrogel with high conductivity and no conductive filler. Figure 1 , specifically including the following steps:

[0033] (1) Preparation of PEDOT:PSS self-supporting film: 2 mL of PEDOT:PSS aqueous solution (model PH1000) was pipetted out by a pipette, and ultrasonicated in a water bath for 5 minutes to mix evenly. A dopant was added to the PEDOT:PSS solution, and the amount of the dopant was 10-50% of the mass of PEDOT:PSS. The mixture was stirred for 15 minutes to obtain a mixed solution. The mixed solution was drop-coated on a polytetrafluoroethylene mold substrate with a size of 50*30*0.4 mm, and dried at room temperature to form a film. After the film was completely dried, the film was peeled off from the polytetrafluoroethylene substrate to obtain a PEDOT:PSS self-supporting film.

[0034] The dopant is lithium bis(trifluoromethylsulfonyl)imide (Li-TFSI).

[0035] (2) Preparation of PEDOT:PSS hydrogel: The PEDOT:PSS self-supporting film was immersed in an ethanol solution for 4 h to remove PSS and thus improve the conductivity. It was then annealed at 130-140°C for 3 times with a cycle of 15 minutes. The self-supporting film was then immersed in an antifreeze aqueous solution for 30-60 seconds to obtain a high conductivity antifreeze organic hydrogel. The mass concentration of the antifreeze aqueous solution was 0-100%.

[0036] Wherein, the antifreeze agent is one or more of propylene glycol, ethylene glycol and polyethylene glycol.

[0037] (3) The prepared high conductivity antifreeze organic hydrogel is used to prepare thermoelectric devices.

[0038] The prepared high-conductivity antifreeze organic hydrogel is cut into long strips, and the long strips of hydrogel are connected by conductive silver paste and copper foil to prepare a thermoelectric device.

[0039] The following are specific embodiments.

[0040] Example 1

[0041] (1) Preparation of PEDOT:PSS self-supporting film: 2 mL of PEDOT:PSS aqueous solution was pipetted with a pipette and ultrasonicated in a water bath for 5 minutes to remove aggregated particles of PEDOT:PSS. 50% of the weight of dopant Li-TFSI relative to PEDOT:PSS was added to the PEDOT:PSS solution and stirred at room temperature for 15 minutes. The uniformly stirred mixed solution was drop-coated on a polytetrafluoroethylene mold substrate with a size of 50*30*0.4 mm. The solution was dried at room temperature to form a film. After the film was completely dried, it was peeled off from the polytetrafluoroethylene substrate to obtain a PEDOT:PSS self-supporting film.

[0042] (2) Preparation of high conductivity antifreeze PEDOT:PSS hydrogel: The PEDOT:PSS self-supporting film prepared in step (1) was immersed in an anhydrous ethanol solution for 4 hours, and then annealed at 140°C for 15 minutes, and the cycle was repeated 3 times. The self-supporting film was immersed in a 100 wt.% propylene glycol aqueous solution for 30 seconds, and the liquid on the surface was wiped off to obtain a PEDOT:PSS hydrogel, which is a high conductivity antifreeze organic hydrogel.

[0043] (3) Preparation of hydrogel thermoelectric devices: The prepared high-conductivity antifreeze organic hydrogel is cut into long strips, and the long strips of hydrogel are connected by conductive silver paste and copper foil to prepare thermoelectric devices, see Figure 7 .

[0044] See also Figure 6 ,It can be seen that the conductivity of the high conductivity antifreeze organic hydrogel changes little from room temperature to -90 °C, indicating that the change in temperature has almost no effect on the electrical properties of the hydrogel.

[0045] Example 2

[0046] The difference from Example 1 is that the concentration of the glycerol aqueous solution in Example 2 is 0 wt.%.

[0047] Example 3

[0048] The difference from Example 1 is that the concentration of the glycerol aqueous solution in Example 3 is 10 wt.%.

[0049] Example 4

[0050] The difference from Example 1 is that the concentration of the glycerol aqueous solution in Example 4 is 30 wt.%.

[0051] Example 5

[0052] The difference from Example 1 is that the concentration of the glycerol aqueous solution in Example 5 is 50 wt.%.

[0053] Example 6

[0054] The difference from Example 1 is that the concentration of the glycerol aqueous solution in Example 6 is 70 wt.%.

[0055] Example 7

[0056] The difference from Example 1 is that the concentration of the glycerol aqueous solution in Example 7 is 90 wt.%.

[0057] Example 8

[0058] The difference from Example 1 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 10% of the mass of PEDOT:PSS.

[0059] Example 9

[0060] The difference from Example 1 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 20% of the mass of PEDOT:PSS.

[0061] Example 10

[0062] The difference from Example 1 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 30% of the mass of PEDOT:PSS.

[0063] Embodiment 11

[0064] The difference from Example 1 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 40% of the mass of PEDOT:PSS.

[0065] Example 12

[0066] The difference from Example 1 is that annealing is performed at 130° C. for 15 minutes.

[0067] Example 13

[0068] The difference from Example 1 is that annealing is performed at 135° C. for 15 minutes.

[0069] Embodiment 14

[0070] The difference from Example 1 is that the self-supporting film is immersed in a 100 wt. % glycerol aqueous solution for 40 seconds.

[0071] Embodiment 15

[0072] The difference from Example 1 is that the self-supporting film is immersed in a 100 wt. % glycerol aqueous solution for 50 seconds.

[0073] Example 16

[0074] The difference from Example 1 is that the self-supporting film is immersed in a 100 wt. % glycerol aqueous solution for 60 seconds.

[0075] Embodiment 17

[0076] (1) Preparation of PEDOT:PSS self-supporting film: 2 mL of PEDOT:PSS was taken out by pipette, and ultrasonicated in a water bath for 5 minutes. 50% of the weight of the dopant Li-TFSI was added to the PEDOT:PSS solution, and stirred at room temperature for 15 minutes. The mixed solution was dropped onto a polytetrafluoroethylene mold substrate with a size of 50*30*0.4 mm, and the solution was dried at room temperature to form a film. When the film was completely dry, it was peeled off from the polytetrafluoroethylene substrate to obtain a PEDOT:PSS self-supporting film.

[0077] (2) Preparation of high conductivity antifreeze PEDOT:PSS hydrogel: The PEDOT:PSS self-supporting film prepared in step (1) was immersed in anhydrous ethanol solution for 4 hours, and then annealed at 140°C for 15 minutes, and the cycle was repeated 3 times. The self-supporting film was immersed in a 100 wt.% ethylene glycol aqueous solution for 30 seconds, and the surface moisture was wiped off to obtain a PEDOT:PSS hydrogel, which is a high conductivity antifreeze organic hydrogel.

[0078] (3) Preparation of hydrogel thermoelectric devices: The prepared high-conductivity hydrogel is cut into long strips, and the long strips of hydrogel are connected by conductive silver paste and copper foil to prepare thermoelectric devices.

[0079] Embodiment 18

[0080] The difference from Example 17 is that the concentration of the ethylene glycol aqueous solution in Example 18 is 0 wt.%.

[0081] Embodiment 19

[0082] The difference from Example 17 is that the concentration of the ethylene glycol aqueous solution in Example 19 is 10 wt.%.

[0083] Embodiment 20

[0084] The difference from Example 17 is that the concentration of the ethylene glycol aqueous solution in Example 20 is 30 wt.%.

[0085] Embodiment 21

[0086] The difference from Example 17 is that the concentration of the ethylene glycol aqueous solution in Example 21 is 50 wt.%.

[0087] Embodiment 22

[0088] The difference from Example 17 is that the concentration of the ethylene glycol aqueous solution in Example 22 is 70 wt.%.

[0089] Embodiment 23

[0090] The difference from Example 17 is that the concentration of the ethylene glycol aqueous solution in Example 23 is 90 wt.%.

[0091] Embodiment 24

[0092] The difference from Example 17 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 10% of the mass of PEDOT:PSS.

[0093] Embodiment 25

[0094] The difference from Example 17 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 20% of the mass of PEDOT:PSS.

[0095] Embodiment 26

[0096] The difference from Example 17 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 30% of the mass of PEDOT:PSS.

[0097] Embodiment 27

[0098] The difference from Example 17 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 40% of the mass of PEDOT:PSS.

[0099] Embodiment 28

[0100] The difference from Example 17 is that annealing is then performed at 130° C. for 15 minutes.

[0101] Embodiment 29

[0102] The difference from Example 17 is that annealing is then performed at 135° C. for 15 minutes.

[0103] Embodiment 30

[0104] The difference from Example 17 is that the self-supporting film is immersed in a 100 wt. % ethylene glycol aqueous solution for 40 seconds.

[0105] Embodiment 31

[0106] The difference from Example 17 is that the self-supporting film is immersed in a 100 wt. % ethylene glycol aqueous solution for 50 s.

[0107] Embodiment 32

[0108] The difference from Example 17 is that the self-supporting film is immersed in a 100 wt. % ethylene glycol aqueous solution for 60 s.

[0109] Embodiment 33

[0110] (1) Preparation of PEDOT:PSS self-supporting film: 2 mL of PEDOT:PSS was taken out by pipette, and ultrasonicated in a water bath for 5 minutes. 50% of the weight of the dopant Li-TFSI was added to the PEDOT:PSS solution, and stirred at room temperature for 15 minutes. The mixed solution was dropped onto a polytetrafluoroethylene mold substrate with a size of 50*30*0.4 mm, and the solution was dried at room temperature to form a film. When the film was completely dry, it was peeled off from the polytetrafluoroethylene substrate to obtain a PEDOT:PSS self-supporting film.

[0111] (2) Preparation of high conductivity antifreeze PEDOT:PSS hydrogel: The PEDOT:PSS self-supporting film prepared in step (1) was immersed in an anhydrous ethanol solution for 4 hours, and then annealed at 140°C for 15 minutes, and the cycle was repeated 3 times. The self-supporting film was immersed in a 100 wt.% polyethylene glycol aqueous solution for 30 seconds, and the surface moisture was wiped off to obtain a PEDOT:PSS hydrogel, which is a high conductivity antifreeze organic hydrogel.

[0112] (3) Preparation of hydrogel thermoelectric devices: The prepared high-conductivity hydrogel is cut into long strips, and the long strips of hydrogel are connected by conductive silver paste and copper foil to prepare thermoelectric devices.

[0113] Embodiment 34

[0114] The difference from Example 33 is that the concentration of the polyethylene glycol aqueous solution in Example 34 is 0 wt.%.

[0115] Embodiment 35

[0116] The difference from Example 33 is that the concentration of the polyethylene glycol aqueous solution in Example 35 is 10 wt.%.

[0117] Embodiment 36

[0118] The difference from Example 33 is that the concentration of the polyethylene glycol aqueous solution in Example 36 is 30 wt.%.

[0119] Embodiment 37

[0120] The difference from Example 33 is that the concentration of the polyethylene glycol aqueous solution in Example 37 is 50 wt.%.

[0121] Embodiment 38

[0122] The difference from Example 33 is that the concentration of the polyethylene glycol aqueous solution in Example 38 is 70 wt.%.

[0123] Embodiment 39

[0124] The difference from Example 33 is that the concentration of the polyethylene glycol aqueous solution in Example 39 is 90 wt.%.

[0125] Example 40 is different from Example 33 in that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 10% of the mass of PEDOT:PSS.

[0126] Embodiment 41

[0127] The difference from Example 33 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 20% of the mass of PEDOT:PSS.

[0128] Embodiment 42

[0129] The difference from Example 33 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 30% of the mass of PEDOT:PSS.

[0130] Embodiment 43

[0131] The difference from Example 33 is that a dopant Li-TFSI is added to the PEDOT:PSS solution in an amount of 40% of the mass of PEDOT:PSS.

[0132] Embodiment 44

[0133] The difference from Example 33 is that annealing is then performed at 130° C. for 15 minutes.

[0134] Embodiment 45

[0135] The difference from Example 33 is that annealing is then performed at 135° C. for 15 minutes.

[0136] Embodiment 46

[0137] The difference from Example 33 is that the self-supporting film is immersed in a 100 wt. % polyethylene glycol aqueous solution for 40 s.

[0138] Embodiment 47

[0139] The difference from Example 33 is that the self-supporting film is immersed in a 100 wt. % polyethylene glycol aqueous solution for 50 s.

[0140] Embodiment 48

[0141] The difference from Example 33 is that the self-supporting film is immersed in a 100 wt. % polyethylene glycol aqueous solution for 60 s.

[0142] Figure 2 (a), (b) and (c) show the thermoelectric properties of PEDOT:PSS organic hydrogels prepared with different concentrations of antifreeze agents propylene glycol, polyethylene glycol and ethylene glycol aqueous solution, respectively. It can be seen that with the increase of the concentration of propylene glycol, polyethylene glycol and ethylene glycol aqueous solution, the conductivity of PEDOT:PSS organic hydrogel increases. When the concentration of propylene glycol solution is 100wt.%, the conductivity of the organic hydrogel reaches a maximum value, and the maximum conductivity is 698.26S / cm, which is higher than the hydrogel currently prepared by polymer materials. When the concentration of polyethylene glycol solution is 100wt.%, the conductivity of the organic hydrogel reaches a maximum value, and the maximum conductivity is 728.51S / cm, which is higher than the hydrogel currently prepared by polymer materials. The Seebeck coefficient of the obtained hydrogel is a positive value, such as Figure 2 As shown in (b), the prepared PEDOT:PSS hydrogel is a p-type material, and the Seebeck coefficient of the hydrogel first increases and then decreases with the increase of the concentration of the antifreeze aqueous solution.

[0143] The conductivity of the prepared organohydrogel is higher than the values ​​in the literature, such as Figure 3 shown.

[0144] Scanning electron microscopy images of the cross section of the organohydrogel after freeze drying show that when the self-supporting film is immersed in an antifreeze aqueous solution of a certain concentration, the antifreeze solution exists in the porous structure, e.g. Figure 4 As shown in (a), (b) and (c).

[0145] The differential scanning calorimetry spectrum of the antifreeze high conductivity antifreeze organic hydrogel is shown in Figure 5 As shown, the solidification point of the hydrogel when immersed in a 100wt.% EG solution is -37.8°C, the glass transition temperature of the hydrogel when immersed in a 100wt.% PEG solution is -57.5°C, and the glass transition temperature of the hydrogel when immersed in a 100wt.% glycerol solution is -92.2°C.

[0146] The conductivity of the high-conductivity antifreeze organohydrogel prepared in Example 1 can be well maintained from room temperature to -90°C, and the conductivity remains substantially unchanged as the temperature decreases.

[0147] Since the organic hydrogel has high electrical conductivity, the present invention prepares the hydrogel into a thermoelectric device, and fixes the hot end of the device to room temperature, and the cold end of the device to a temperature below room temperature, so that the temperature difference of the device reaches 13K, 25K, 32K, 46K, 61K, and 102K respectively, and tests the performance of the device. Figure 8 As shown in (a), (b) and (c), this hydrogel has a maximum output power of 426nW at a temperature difference of 102K.

[0148] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0149] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a high conductivity antifreeze organic hydrogel, characterized in that: The following steps are involved: The PEDOT:PSS aqueous solution is mixed with the dopant, then drop-coated on a substrate and dried to obtain a PEDOT:PSS free-standing film; After annealing, the PEDOT:PSS self-supporting film was immersed in an aqueous solution of an antifreeze agent to obtain a high conductivity antifreeze organic hydrogel.

2. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: The amount of dopant used is 10-50% of the mass of PEDOT:PSS.

3. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: The dopant is lithium bis(trifluoromethylsulfonyl)imide.

4. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: The antifreeze agent is glycerol, ethylene glycol or polyethylene glycol.

5. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: The concentration of the aqueous solution of the antifreeze agent is 0wt.%-100wt.%.

6. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: Before annealing the PEDOT:PSS self-supporting film, the PEDOT:PSS self-supporting film was immersed in ethanol.

7. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: The annealing conditions are: 130-140° C., 15 minutes per cycle, and annealing is performed three times.

8. The method for preparing the high conductivity antifreeze organic hydrogel according to claim 1, characterized in that: After annealing, the PEDOT:PSS self-supporting film is immersed in an aqueous solution of an antifreeze agent for 30-60 seconds.

9. A high conductivity antifreeze organic hydrogel prepared according to the method according to any one of claims 1 to 8, characterized in that: The maximum conductivity of the organohydrogel is 728.51 S / cm.

10. A thermoelectric device, characterized in that: The invention comprises a high-conductivity antifreeze organic hydrogel prepared according to the method described in any one of claims 1 to 8.